Research on Regional Economic Development of Guangxi Based on Multiple Statistic Analysis - Jian Xin; Weizhang Lai (Research and Social Study Institute, 2021)
Economic development is a prerequisite for social stability and development. However, the regional economic development in various regions of our country is unbalanced, especially in the western region. As one of the minority autonomous regions in western of my country, Guangxi Province is undoubtedly of great practical significance to study its regional economic development. In this context, this paper is based on 8 economic indicators and related economic data of 14 cities in Guangxi Province in 2018, and is based on the theory of dimensionality reduction methods and cluster analysis, using principal component analysis (PCA) and hierarchical clustering methods to assess the comprehensive level of Guangxi’s economic development. The result shows that most cities' economic development in Guangxi Province is great. However, there are signature differences in economic development between urban areas.